Risk Analysis of a Railway Station in Shenyang with Cover Excavation and Top-Down Method. Issue 1 (February 2020) - Wang, Fengchi; Chen, Jiaxi; Wen, Yizhen
Abstract: In this paper, for the water-rich sandy soil layer, ABAQUS finite element software is used to simulate the actual engineering background and the impact of different construction stages on different risk terms. The results shown that the settlement curve shows a large amount of soil settlement near the foundation pit, far the tendency of the settlement of the soil at the foundation pit is smaller; during the construction process, the vertical stress distribution of the entire soil changes; as the excavation depth of the subway station gradually increases, the settlement of the hotel increases accordingly, and The amount of settlement near the station side is always greater than that far from the station side; the force form of the ground connecting wall is consistent with the simplified diagram of the equivalent beam theory. And as the excavation depth of the foundation pit increases, the position of the earth pressure zero point gradually decreases.